Chapter 10 Designing for Mental Health Psychiatry, Psychology and the Architectural Study Project (Springer Nature, 2019)
In 1953 the American Psychiatric Association established an Architectural Study Project in collaboration with the American Institute of Architects. The project brought together a wide range of experts from psychiatry and the behavioural sciences and the planning and design professions to provide solutions to the ailing mental hospital system in North America. They began to focus attention on various aspects of the hospital environment, such as light, colour and the creation of spaces for privacy and social contact, in ways that would go on to influence theories, methods and designs far beyond the walls of the institution. This paper will explore the contribution of the mental hospital, as both laboratory and field site, to the development of the new field of environmental psychology which attended to the function and design of a range of city spaces to prevent mental illness and promote mental health in a period of urban crisis.